Comparative Study of Predicting Heart Disease By Means Of Data Mining (International Journal of Engineering and Computer Science, 2016)
At the present time all the activities are done in the world through internet. The use of computer in the fieldsof medicine are highly improved. The computerized hospital includes the activities like treatment of illnesses, maintain the patient’s information up-to-date that leads to handle huge amount of data regularly. It is very difficult to handle the large amount of data for predicting the heart disease. Data mining approach is a good way for predicting the heart disease at minimum effort.This paper analyses the existing prediction system and discussing the various disputes on the existing system.  The result of this paper helps the health consultants to diagnose the disease in less time and predict the probable problems well in advance and save the patient life.